Large scale PIV-measurement to evaluate the flow isolation device (FID) efficiency in the stocker room of wafer masks. (November 2022) - Lin, Tee; Zargar, Omid Ali; Lin, Che-Yu; Lai, Ting-Jun; Shih, Yang-Cheng; Hu, Shih-Cheng; Leggett, Graham
Abstract: Silicon chip demand increased in recent years while the linewidth of the integrated circuits (ICs) has decreased. Improvement of the wafer process yield has become a key factor in chip manufacturing. The yield of the wafer process is closely related to the quality of the mask in the lithography process. The environmental conditions of the mask stocker room need to be carefully monitored and controlled to maintain the mask quality. The moist air invasion from the stocker room when the mask box exchange door is open can significantly increase the internal ambient humidity. This humidity leads to mask defects. Therefore, the moist air invasion from the stocker room should be minimized. In this study, an innovative flow isolation device (FID) is designed and manufactured. This device is used to block the flow of air through the mask exchange door. Smoke flow visualization and particle image velocimetry (PIV) were performed to evaluate the FID performance. The experimental results show that when the pressure of the stocker room is 0.3 Pa and the face velocity of FID is 2.0 m/s, the isolation efficiency is around 83.03%. The newly designed FID can significantly reduce the volume of CDA used during manufacturing. This can significantly reduce waste and energy cost.